Novelist as a vocation - Murakami, Haruki (London Harvill Secker, 2022)
In this engaging book, the internationally best-selling author and famously reclusive writer shares with readers what he thinks about being a novelist; his thoughts on the role of the novel in our society.
Keywords: Murakami, Haruki